2011
DOI: 10.1016/j.jhsa.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes and Complications of Treating Unstable Distal Radius Fractures in the Elderly

Abstract: Purpose As the population in developed countries continues to age, the incidence of osteoporotic distal radius fractures (DRFs) will increase as well. Treatment of DRF in the elderly population is controversial. We systematically reviewed the existing literature for the management of DRFs in patients 60 and over with five common techniques: volar locking plate system (VLPS), non-bridging external fixation (non-BrEF), bridging external fixation (BrEF), percutaneous Kirschner-wire fixation (PKF), and cast immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
246
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 319 publications
(270 citation statements)
references
References 65 publications
6
246
0
18
Order By: Relevance
“…273 Care of the patient with a distal radius fracture is also costly: A cost of US$7788 (between years 2000 and 2005) has been estimated for a Medicare patient with a distal radius fracture. 274 Despite their frequency, treatment of distal radius fractures in elderly patients is controversial 275 …”
Section: Distal Radius Fractures Simon C Mears Md Phd (Harry Hoyenmentioning
confidence: 99%
“…273 Care of the patient with a distal radius fracture is also costly: A cost of US$7788 (between years 2000 and 2005) has been estimated for a Medicare patient with a distal radius fracture. 274 Despite their frequency, treatment of distal radius fractures in elderly patients is controversial 275 …”
Section: Distal Radius Fractures Simon C Mears Md Phd (Harry Hoyenmentioning
confidence: 99%
“…Maintenance of satisfactory alignment is difficult. 6,7,8,9 Recent studies indicate high rate of re-displacement, reangulation and remanipulation following closed reduction and cast immobilization. 8,9 Supplementary percutaneous K-wire fixation resulted in a significantly better maintenance of the alignment of the completely displaced fractures of the distal radius.…”
Section: Introductionmentioning
confidence: 99%
“…This focus aligns well with the target audience being orthopedic surgeons. Health policymakers, funders, and clinicians should be aware that as the guidelines do not address function, 14 they are not appropriate for rehabilitation professionals or other groups who are focused on functional outcomes. CPG may be developed by multidisciplinary teams and should address comprehensive management or be very focused on a specific intervention or target user.…”
Section: Discussionmentioning
confidence: 99%
“…6 Study shows that more than 640 000 cases of DRF were reported during 2001 in North America, 14 and nearly 372 000 individuals of age 65 years and older sustain DRF every year in the United States. 35 Many studies describe the extent of impairments and disabilities experienced by the patients with DRF.…”
Section: Introductionmentioning
confidence: 99%